Clinical Evaluation of a Novel Formulation: Banarasi Tambula (Piper Betle L.) Patra Swarasa with Bhimseni Karpura Choorna (Dryobalanops Aromatica Gaertn.F.) in the Management of Kaphaja Kasa (Productive Cough) - Naik, Shubhankar Mukund; Kore, Sharayu (International Research Journal of Ayurveda & Yoga, 2022)
During high waves of SARS Covid-19 and post-covid period there is increase in respiratory tract diseases in population. It was noted that Ayurvedic management was having encouraging results with comparative cure rate higher and with lesser complications. ‘Tambula Patra (Betel leaf) along with Bhimseni Karpura’ (Camphor) is one of the commonest combination drug of choice used especially in Kapha dominant Kasa by Vruddha Vaidyas from a long period of time. The preparation was named as “NagaSphatika” based on combination of basonym and synomym of components. It was made using Banarasi Tambula leaf’s Swarasa with Bhimseni Karpura as a Prakshepa (additive) in liquid form dispensable medicine for Kaphaja Kasa. Single arm Clinical study was undertaken to evaluate its efficacy in Kaphaja Kasa in 52 patients. NagaSphatika was significantly effective in the management of Kaphaja Kasa. The disease involves Kapha and Vata dosha dushti predominantly. Tambula due to its Katu, Tikta, Kashaya rasa, Ushna Virya, Katu Vipaka, Laghu, Ruksha, Tikshna and Vishada guna pacifies Kapha Dosha leading to removal of Avarodh in the Srotas bringing Prakruta gati to Vata Dosha and also ignites Agni which further digests the Ama or Dushta Rasa Dhatu. Bhimseni Karpura having Tikta, Katu Rasa, Madhura Rasa and Katu Vipaka, Laghu, Tikshna Guna alleviates Kapha Dosha by its Lekhan Karma occurring in Kantha and Urah. NagaSphatika had significant effects on signs and symptoms of Kaphaja Kasa, hence is effective in its management.